Green Finance Instruments, FinTech, and Investment Strategies Sustainable Portfolio Management in the Post-COVID Era - Naifar, Nader; Elsayed, Ahmed (Sustainable Finance, 2023)
XII, 300 p. 25 illus., 24 illus. in color.